Respuesta :

Step-by-step explanation:

the first one is:

2 so not th second one

Answer:

Step-by-step explanation: We can solve this in two ways:  Solve the equations directly, or graph the lines and find the point they intersect (which will be the only point at which they are equal.

Solve The Equations:

y = 2x+9

y = -x-3

Set them equal to each other (to find x such that both equations will return the same value for y).

-x-3 = 2x + 9

-3x = 12

x = -4

Use x=-4 in either equation to find y:

y = -x-3

y = -(-4)-3

y = 1

===

The point is (-4,1).  That is the point that satisfies both equations:

1)  y = 2x+9

    y = 2(-4)+9

   y = 1, and

2)  y = -x-3

    y = -(-4)-3

    y = 1

=====

We can also solve by graphing and finding the point at which the two lines intersect.  A graph is attached.

Ver imagen rspill6